The Royal Wedding Reimagined: Textual Criticism and Interpretation of Psalm 45's Superscription - Taghavi, Hadi; Haghighatkhah, Amirreza (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2025)
The article presents a critical edition and exegesis of Psalm 45’s superscription, examining its textual, lexical, and semantic dimensions. Through analysis of ancient versions, it reassesses key terms (לבני־קרח, ידידות למנצח על ששנים), proposes alternative readings, and suggests a revised heading, highlighting prophetic-messianic links and the superscription’s role in illuminating the Psalm’s themes and characters.